Keanekaragaman Jenis Burung di Cagar Alam Wolo Tadho, Kabupaten Ngada, Provinsi Nusa Tenggara Timur - Desi Meriati Maring; Ludji Michael Riwu Kaho; Fadlan Pramatana; Roni Haposan Sipayung (Wana Lestari, 2026)
This research has been carried out in the Wolo Tadho Nature Reserve, Riung District, Ngada Regency, East Nusa Tenggara Province in July - August 2023. This study was conducted to determine the level of bird species diversity in the Wolo Tadho Nature Reserve based on height and land cover. The methods used for bird species diversity and vegetation analysis in this study are the point count method and the path or transect method which is determined by purposive sampling based on the type of land cover and altitude. The data obtained were calculated using the Shannon-Wiener Type Diversity Index (H'), Evenness Index (E), and Important Value Index. The results of the study show that there are 22 species of birds found in the Wolo Tadho Nature Reserve from 20 families with a total of 335 individuals. The results of the calculation of bird species diversity in CA Wolo Tadho are classified as moderate with a value of H'=2.666. Based on land cover, the diversity of bird species is highest in the savanna habitat type with a value of 2.443 and the lowest in the vacant land habitat type with a value of 1.742. Based on altitude, the value of bird species diversity was highest at height I with a value of 2.744 and the lowest at height V with a value of 2.021. The results of vegetation analysis showed that the highest INP at the tree level was Acid (Tamarindus indica) at 49.12%. while the lowest is Kedondong Hutan (Spondias pinnata) with a value of 2.36%. At the pole level, the highest INP is acid (Tamarindus indica) with an INP of 48.07% and the lowest INP is melinjo (Gnetum gnemon L) with a percentage of 0.76%. At the stake level, the highest INP is lamtoro (Leucaena leucocephala) with an INP of 37.45% and the lowest INP is forest kedondong (Spondias pinnata) with an INP value of 0.86%. At the seedling level, the highest INP is forest mango (Mangifera indica) with the highest INP of 35.88% and the lowest INP is white teak (Gmelina arborea) with an INP of 1.83%.